A Photocrosslinking‐Based RNA Chemical Proteomics Approach to Profile m6A‐Regulated Protein‐RNA Interactions. Issue 1 (8th November 2018) - Arguello, A. Emilia; Srikumar, Tharan; Kleiner, Ralph E.
Abstract: Post‐transcriptional modifications play an important role in RNA biology. In particular, the addition of small chemical groups to the nucleobases of mRNA can affect how modified transcripts are processed in the cell, thereby impacting gene expression programs. In order to study the molecular mechanisms underlying these modifications, it is necessary to characterize their 'readers', that is, proteins that directly bind to these modifications to mediate their functional consequences; this is a major challenge because we lack approaches to precisely manipulate RNA chemistry in the cell and because protein–modified RNA interactions can be low affinity. In this unit, we describe in detail a photocrosslinking‐based RNA chemical proteomics approach to profile the protein–modified RNA interactome modulated by N 6 ‐methyladenosine (m 6 A), the most abundant internal modification in eukaryotic mRNA. First, we present protocols for the synthesis and characterization of short, diazirine‐containing synthetic RNA probes, followed by a description of their use in mass spectrometry–based proteomics with HeLa cell lysate and a short commentary on data analysis and result interpretation. © 2018 by John Wiley & Sons, Inc.